Evaluation of the accordance of panoramic radiography ordering in maxillofacial radiology department, school of dentistry, Tehran university of medical sciences with FDA guidelines in scholar year 200 - Goodarzi Pour D.; Bashizade H.; Talaeipour AR; Najafi Motlagh A. (Tehran University of Medical Sciences, 2007)
Background and Aim: The goal of dental treatment is to improve oral hygiene, to maintain teeth and minimize the risk of diseases. Although data obtained from radiographs has distinct advantages to patients, the radiation side effects should be considered as well. FDA has developed a guideline for prescribing radiographs in the middle of the eighties. The aim of this study was to evaluate the reasons of ordering panoramic radiographs and their accordance with FDA guidelines in Tehran dental school. Materials and methods: This descriptive study was carried out on 250 patients referred from different departments of Tehran dental school to radiology department for panoramic radiography. Chief complaints and clinical findings of patients were recorded in a check list and compared with the FDA guidelines prescribed. Results: Our findings showed that prescription of panoramic radiographs were in accordance with FDA guidelines in 97.2% of cases. Conclusion: Based of the results of this study, the trend of panoramic radiography ordering in the dental school of Tehran university is adequate. This may be attributed to the academic field of this study.